Technology developments the role of mechanism and machine science and IFToMM - Ceccarelli, Marco; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This is the first book of a series that will focus on MMS (Mechanism and Machine Science). This book also presents IFToMM, the International Federation on the Promotion of MMS and its activity. This volume contains contributions by IFToMM officers who are Chairs of member organizations (MOs), permanent commissions (PCs), and technical committees (TCs), who have reported their experiences and views toward the future of IFToMM and MMS. The book is composed of three parts: the first with general considerations by high-standing IFToMM persons, the second chapter with views by the chairs of PCs and TCs as dealing with specific subject areas, and the third one with reports by the chairs of MOs as presenting experiences and challenges in national and territory communities. This book will be of interest to a wide public who wish to know the status and trends in MMS both at international level through IFToMM and in national/local frames through the leading actors of activities. In addition, the book can be considered also a fruitful source to find out who's who in MMS, historical backgrounds and trends in MMS developments, as well as for challenges and problems in future activity by IFToMM community.
Preface -- 1. General Considerations -- Activity and trends in MMS from IFToMM community, by Marco Ceccarelli -- Promoting novel approaches of MMS for sustainable energy Applications, by Ion Visa -- Role of MMS and IFToMM in Iberomaerican community and open perspectives, by Emilio Bautista Paz and Justo Nieto Nieto -- India's contributions over the last 40 years in Turbine Blade dynamics, by Jammi S. Rao -- A brief history of legged Robotics, by P.J. Csonka and Kenneth J. Waldron -- 2. Viewpoints by Chairs of IFToMM Technical Committees and Permanent Commissions -- The History of Mechanism and Machine Science (HMMS) and IFToMM's Permanent Commission for HMMS, by Teun Koetsier, Hanfried Kerle, Hong-Sen Yan -- On the development of an electronic dictionary for IFToMM by Antonius J Klein-Breteler -- The role of mechanism models for motion generation in mechanical engineering, by Hanfried Kerle, Burkhard Corves, Klaus Mauersberger, Karl-Heinz Modler -- Development of Computational Kinematics within the IFToMM Community, by Doina Pisla and Manfred L. Husty -- Theory and practice of gearing in MMS, by Veniamin I. Goldfarb -- ThinkMOTION: Digital Mechanism and Gear Library goes Europeana, by Burkhard CORVES, Torsten BRIX, Ulf Döring -- Micromachines: the role of the mechanisms community, by G.K. Ananthasuresh -- Role of MMS and IFToMM in Multibody Dynamics, by Javier Cuadrado, Jose Escalona, Werner Schiehlen, Robert Seifried -- State-of-the-art and trends of development of reliability of machines and mechanisms, by Irina V. Demiyanushko -- Role of MMS and IFToMM in Robotics and Mechatronics, by I-Ming Chen -- Role of MMS and IFToMM in the creation of novel automotive transmissions and hybrids, by Madhusudan Raghavan -- Advancements and future of Tribology from IFToMM, by Jianbin Luo -- 3. Experiences and views by IFToMM Member Organizations -- MMS and IFToMM in Armenia: History, Present Trends and Perspectives, by Yuri Sargsyan -- Role of MMS and IFToMM in Belarus by Vladimir Algin -- The Role of ABCM on Engineering and Mechanical Sciences in Brazil and its Relationship with IFToMM, by João Carlos Mendes Carvalho -- Contributions to the Promotion of Mechanism and Machine Science by the IFToMM Canadian Community (CCToMM), by M.J.D. Hayes, R. Boudreau, J.A. Carretero, R.P. Podhorodesk -- Some Recent Advances in Mechanisms and Robotics in China-Beijing, by Tian Huang -- Role of Mechanism and Machine Science in Taiwan, by Hong-Sen Yan Zhang Hua Fong,Ying Chien Tsai, Cheng Kuo Sung, Jao Hwa Kuang, Chung Biau Tsay, Shyi Jeng Tsai, Dar Zen Chen, Tyng Liu, Jyh Jone Lee Shuo Hung Chang -- Czech contribution to the role of mechanism and machine science and IFToMM, by Miroslav Václavík, Ladislav P-st, Jaromír Horá-ek, Ji-í Mrázek, tefan Sega -- Role of MMS in the development of Mechanical Engineering Research in Georgia, by Nodar Davitashvili -- The Role of MMS (Mechanism and Machine Science) and IFToMM in Greece, by Thomas G. Chondros -- MMS at University level in Hungary within the IFToMM Community, by Elisabeth Filemon -- Developments in the field of Machines and Mechanisms in India over the ages, by C. Amarnath -- Role of MMS and IFToMM in Italy: The influence of IFToMM and MMS in Italian culture of presence by Alberto Rovetta -- Achievements in Machine Mechanism Science in Lithuania, by Vytautas Ostasevicius -- The Mexican Contribution to Mechanism and Machine Science and Technology, by Ricardo Chicurel-Uziel, Alberto Caballero-Ruiz, Leopoldo Ruiz-Huerta, Alfonso Pámanes-García -- The Significance and Role of IFToMM Poland in the Creative Development of Mechanism and Machine Science, by Józef Wojnarowki -- The Romanian Association for the Mechanisms and Machines Science Past, Present and Future, by Ion Visa -- Formation and development of MMS in Russia with participation of Russia in IFToMM activity, by Nikolay V. Umnov and Victor A. Glazunov -- Role of MMS and IFToMM in Slovakia by S. Segla, P. Solek -- The role of MMS and IFToMM influence in Spain, by Fernando Viadero, Vicente Díaz, A. Fernández and A. Gauchía -- Ultra High Precision Robotics: a potential attractive area of interest for MM and IFToMM, by Reymond Clavel, Bérangère Le Gall, Mohamed Bouri -- Teaching and research in mechanism theory and robotics in Tunisia, by Lotfi Romdhane. A. Mlika -- Contributions to MMS and IFToMM from USA, by Kenneth J. Waldron
Includes bibliographical references.
Electronic reproduction.
Keywords: Mechanical engineering